(untitled) - Muller, Nathan J. (New York, 2003)
The book provides the insights that only a veteran with real-world experience can offer, including: Why design is one-half the battle and implementation is the other; Secrets of successful financial planning; How to effectively negotiate service agreements; The role of the communications department, The most effective way to manage, evaluate, and schedule technical staff
Keywords: Computer networks; Management,Handbooks, manuals, etc